2007
DOI: 10.1513/pats.200703-040br
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Outcome Measures for the New Era of Drug Development in Cystic Fibrosis

Abstract: The growing pipeline of candidate drugs for cystic fibrosis (CF) is challenging clinical trial research. There has been a shift from evaluating drugs aimed at treating the secondary manifestations of CF to evaluating drugs targeted toward the primary prevention of chronic lung disease. As CF is an orphan disease, there is a fundamental need to assess new therapies efficiently and accurately by mechanisms that best use the number of available patients. This need can be addressed with the continued advancement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 97 publications
0
66
0
Order By: Relevance
“…The keynote presentation of that workshop identified the following four key characteristics for evaluating CF outcome measures: ''(i) clinical and biological relevance; (ii) sensitivity and specificity to treatment effects; (iii) reproducibility; and (iv) feasibility'' (26). The feasibility of HP noble gas MRI for the evaluation of lung abnormalities in CF patients has been demonstrated in many studies, beginning with a HP 3 He MRI study by Donnelly et al that observed lung ventilation defects in four subjects with moderate to severe CF (27).…”
Section: Discussionmentioning
confidence: 99%
“…The keynote presentation of that workshop identified the following four key characteristics for evaluating CF outcome measures: ''(i) clinical and biological relevance; (ii) sensitivity and specificity to treatment effects; (iii) reproducibility; and (iv) feasibility'' (26). The feasibility of HP noble gas MRI for the evaluation of lung abnormalities in CF patients has been demonstrated in many studies, beginning with a HP 3 He MRI study by Donnelly et al that observed lung ventilation defects in four subjects with moderate to severe CF (27).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, HMGB1 was intermediately elevated in outpatients with CF, in whom neutrophilic inflammation is also evident (but to a lesser extent), and was inversely correlated with lung function when both outpatients and inpatients with CF were considered, which supports the notion that extracellular HMGB1 levels are correlated with overall disease activity and are particularly sensitive to the presence of acute lung inflammation. The potential indicators of CF APE are an area of significant interest because they may be useful biomarkers for novel CF therapeutics and assist in the clinical management of subjects with CF (47,48). The potential to combine the detection of upstream mediators, such as HMGB1, IL-8, and other proteases indicative of acute inflammation, with downstream events, such as the liberation of PGP, might allow the monitoring of both early and late pathways underlying lung inflammation and improve the characterization of CF APE beyond typical clinical criteria.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of a growing pipeline of drugs, including treatments targeting the basic protein defect, which have led to improved lung function, reduced frequency of pulmonary exacerbations, and increased life expectancy (1,2), it is becoming more difficult to demonstrate efficacy with investigational therapies in CF. The CF community has recognized this challenge and emphasized the need to identify and validate biomarkers to serve as prognostic indicators of therapeutic response and outcome measures in earlyphase CF clinical trials (3). Because lung disease is the major determinant of quality of life and survival in CF, and airway inflammation is a hallmark feature of CF lung disease, there is strong rationale to focus the search for relevant pulmonary biomarkers to measures of inflammation.…”
mentioning
confidence: 99%